The Effect of Using the Elsimil Application on the Readiness of Prospective Brides and Grooms in Stunting Mitigation Efforts - Eva Zulisa; Indra Jaya; Rahma Dalila Fitri (GLOBAL HEALTH SCIENCE GROUP, 2025)
Reproductive health is a crucial aspect of preparing for a healthy married life. Sometimes, prospective brides and grooms don't realize the importance of maintaining their health before pregnancy. This lack of knowledge can increase the risk of stunting. Accessing health education and support through mobile apps is an effective way. One application developed by the BKKBN for health screening of prospective brides and grooms is the ‘Elsimil’ (Electronics Ready for Marriage and Pregnancy). The purpose of study was to determine the effectiveness of the use of the ‘Elsimil’ on the readiness of prospective brides and grooms. The type of research is Quasi-experiment with One group pre-posttest design. The sample was taken using a Purposive sampling with a sample size of 36 people. Data collection of health behaviour of prospective brides and grooms using questionnaires to measure the level of knowledge and attitudes of prospective brides and grooms regarding pre-marital health screening as well as observation sheets for monitoring the health of prospective brides and grooms. Data analysis using the Wilcoxon test. The results of this statistical analysis indicate that there is an effect of the use of the ‘Elsimil’ application on the readiness of prospective brides and grooms in stunting mitigation efforts, with the results obtaining a p-value of 0.000.